Chapter 2. Fertilizer Management for Vegetable Production in Florida - Guodong Liu; Eric H. Simonne; Kelly T. Morgan; George J. Hochmuth; Shinsuke Agehara; Rao Mylavarapu; Phillip Williams (EDIS)
Chapter 2 of the Vegetable Production Handbook of Florida